Irbesartan Ameliorates Diabetic Nephropathy by Suppressing the RANKL-RANK-NF-κB Pathway in Type 2 Diabetic db/db Mice - Xiao-Wen Chen; Xiao-Yan Du; Yu-Xian Wang; Jian-Cheng Wang; Wen-Ting Liu; Wen-Jing Chen; Hong-Yu Li; Fen-Fen Peng; Zhao-Zhong Xu; Hong-Xin Niu; Hai-Bo Long (Hindawi Limited, 2016)
The receptor activator of NF-κB ligand (RANKL) and its receptor RANK are overexpressed in focal segmental glomerular sclerosis (FSGS), IgA nephropathy (IgAN), and membranous nephropathy (MN). However, the expression and the potential roles of RANKL and RANK in diabetic nephropathy (DN) remain unclear. Irbesartan (Irb) has beneficial effects against diabetes-induced renal damage, but its mechanisms are poorly understood. Our present study investigated the effects of Irb in DN and whether the renal protective effects of Irb are mediated by RANKL/RANK and the downstream NF-κB pathway in db/db mice. Our results showed that db/db mice revealed severe metabolic abnormalities, renal dysfunction, podocyte injury, and increased MCP-1; these symptoms were reversed by Irb. At the molecular level, RANKL and RANK were overexpressed in the kidneys of db/db mice and Irb downregulated RANKL and RANK and inhibited the downstream NF-κB pathway. Our study suggests that Irb can ameliorate DN by suppressing the RANKL-RANK-NF-κB pathway.